2016
DOI: 10.1007/s12640-016-9690-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gray Matter Volume in Stable Chronic Obstructive Pulmonary Disease with Subclinical Cognitive Impairment: an Exploratory Study

Abstract: Gray matter volume deficits have been identified in cognitively impaired patients with chronic obstructive pulmonary disease (COPD). However, it remains unknown whether the gray matter volume is altered in COPD patients with subclinical cognitive impairment. To determine whether any gray matter abnormalities are present in these patients, neuropsychological tests and structural MRI data were analyzed from 60 patients with COPD and 60 age-, gender-, education-, and handedness-matched normal controls (NCs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Impaired white matter microstructural integrity in COPD patients has been reported by many studies (Dodd et al, ; Spilling, Jones, Dodd, & Barrick, ); van Dijk et al, ). However, the results of GM volume change reported by previous studies are inconsistent (Dodd et al, ; Esser et al, ; Spilling et al, ; Wang et al, ). Some studies revealed that there existed regional or global brain atrophy in COPD patients (Esser et al, ; Wang et al, ), while other studies did not find a significant difference in GM volume between COPD patients and normal controls (Dodd et al, ; Spilling et al, ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Impaired white matter microstructural integrity in COPD patients has been reported by many studies (Dodd et al, ; Spilling, Jones, Dodd, & Barrick, ); van Dijk et al, ). However, the results of GM volume change reported by previous studies are inconsistent (Dodd et al, ; Esser et al, ; Spilling et al, ; Wang et al, ). Some studies revealed that there existed regional or global brain atrophy in COPD patients (Esser et al, ; Wang et al, ), while other studies did not find a significant difference in GM volume between COPD patients and normal controls (Dodd et al, ; Spilling et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…However, the results of GM volume change reported by previous studies are inconsistent (Dodd et al, ; Esser et al, ; Spilling et al, ; Wang et al, ). Some studies revealed that there existed regional or global brain atrophy in COPD patients (Esser et al, ; Wang et al, ), while other studies did not find a significant difference in GM volume between COPD patients and normal controls (Dodd et al, ; Spilling et al, ). In our study, the COPD patients did not demonstrate a significant different GM or WM volume when compared to normal controls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neuroimaging studies showed there are signiicantly lowered gray mater volumes in several brain regions as hippocamp [7], limbic and paralimbic structures [77], precuneus, bilateral calcarine, right superior temporal gyrus/middle temporal gyrus, bilateral fusiform, right inferior parietal lobule [78], cingulate and amygdala [8], dorsolateral prefrontal cortex [77] etc., evidenced by diferent neuroimaging techniques based on magnetic resonance imaging (MRI). Performance accuracy has increased by introducing voxel-based morphometry analysis also based on MRI.…”
Section: Clinical Consequences Of An Afected Cognition; Measure Methodsmentioning
confidence: 99%
“…It also participates in inflammatory responses as a chemokine of immune cells such as monocytes, neutrophils, mast cells, and T lymphocytes. The clinical applications of SAA have been highlighted . SAA increases earlier and more obviously than CRP does during bacterial infections, which also works upon viral infections, so it can be combined with CRP to improve the accuracy of detection .…”
Section: Introductionmentioning
confidence: 99%